O animador contemporâneo no contexto das novas tecnologias e canais de difusão na internet - Porto, Eduardo José Garnacho (2018)
The internet and Social Media appeared with new ways to share and spread audiovisual contents. The animation contents which appear in these ways of share are a constant and extremely diversified. This way the comtemporary animators find subsistence oportunities in the web world. With this Project we intend to present a pilot episode to a web serie, trying to understand how this same web serie will survive through the interne